Penegakan Hukum terhadap Pelaku Pembuat Stiker Menggunakan Foto Orang Lain yang Mengandung Muatan Penghiaan di Sosial Media - Karisma, Siti; Suphia; Laily Mufid, Firda; Tri Budiman, Nanang (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2024)
The object of this research problem is what are the rules for using otherpeople's photos without permission to be used as stickers on socialmedia and what is the implementation of the law against perpetratorswho make stickers using other people's photos that contain insultingcontent on social media. In this research the author uses a normativetype of research by examining applicable norms. The results of thisresearch can be concluded that making stickers using other people'sphotos on social media is a form of action that can result in legalconsequences. When making stickers using other people's photoswithout permission on social media, it is the same as deliberatelybreaking the law by changing electronic information and this act isregulated in article 32 paragraph (1) and also article 27 paragraph (3)of the ITE Law. Implementation of the law against perpetrators whomake stickers using other people's photos containing insulting contenton social media, where the government has regulated and providedprotection for electronic media users, especially on WhatsApp, wherethe provisions in article 45 paragraph (1) of the ITE Law state thatthey will be punished with imprisonment. a maximum of 6 (six) yearswith a maximum fine of IDR 1,000,000,000.00 (one billion) and canalso be subject to article 48 paragraph 1 of the ITE Law which statesthat it can be punished with imprisonment for a maximum of 8 (eight)years with a maximum fine Rp. 2,000,000,000.00 (two billion).